Appraisal of residential satisfaction in double-storey terrace housing in Malaysia: case studies from greater Kuala Lumpur - Mohit, Mohammad Abdul; Al-Khanbashi, Adel Mahfoud Mubarak (2014)
Double-storey terrace housing is considered as a popular housing type among the middleincome people particularly in urban areas. Indeed, empirical studies identified that, an increase in crime rate in urban areas has affected on residents’ satisfaction of landed housing such as double-storey terrace house. In addition, design of double-storey terrace house lacks ventilation and natural lighting which affected on residents’ satisfaction. As a result of residents’ dissatisfaction, double-storey terrace house is found as the most modified housing types in Malaysia. Thus, this paper aims to appraise residential satisfaction in two double-storey terrace neighbourhoods - Taman Sri Rampai and Taman Keramat Permai in Greater Kuala Lumpur. The research objectives were formulated based on a dynamic interaction approach which includes three main processes- cognitive, affective and behavioural. In order to examine and compare the residential satisfaction in two neighbourhoods, five components of double-storey terrace housing - physical features, housing support services, public facilities, social environment and neighbourhood facilities, were analyzed through residents’ perception on level of satisfaction. The recommendations of the study are directed towards identifying factors that can enhance levels of satisfaction among the residents of the two neighbourhoods.